2006
DOI: 10.1530/eje.1.02106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased lipid intake on hormonal responses during aerobic exercise in endurance-trained men

Abstract: In view of the growing health problem associated with obesity, clarification of the regulation of energy homeostasis is important. Peripheral signals, such as ghrelin and leptin, have been shown to influence energy homeostasis. Nutrients and physical exercise, in turn, influence hormone levels. Data on the hormonal response to physical exercise (standardized negative energy balance) after high-fat (HF) or low-fat (LF) diet with identical carbohydrate intake are currently not available. The aim of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
(37 reference statements)
3
34
0
1
Order By: Relevance
“…Since the duration and intensity of exercise strongly affect GH secretion (8,9), this is likely to have influenced diagnostic values. Interestingly, peak GH levels found in control individuals in this study were comparable to earlier studies with similar exercise intensity (7,10). Of note, a linear dose-relationship between exercise intensity and GH secretory response has been suggested in young healthy men (9).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since the duration and intensity of exercise strongly affect GH secretion (8,9), this is likely to have influenced diagnostic values. Interestingly, peak GH levels found in control individuals in this study were comparable to earlier studies with similar exercise intensity (7,10). Of note, a linear dose-relationship between exercise intensity and GH secretory response has been suggested in young healthy men (9).…”
Section: Discussionsupporting
confidence: 89%
“…Of note, a linear dose-relationship between exercise intensity and GH secretory response has been suggested in young healthy men (9). Previous reports indicate that an aerobic exercise duration of at least 20-30 min is required to provoke a relevant GH secretion, whereas a shorter exercise duration may result in comparably high or even higher GH levels if exercise is performed above the aerobic threshold (7,8,10,17). This implies that a certain intensity of exercise may be required over time to optimise diagnostic accuracy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While long-term exercise resulting weight loss increases plasma ghrelin level [15,16], short-term running, cycling, or rowing exercise does not alter plasma total ghrelin [17][18][19][20][21][22][23] . A few papers, however, reported that plasma total ghrelin level decreased [24][25][26] or increased [27][28][29] during short-term exercise. Schmidt et al [22] reported that there were no correlations between total ghrelin levels and either of treadmill exercise at 50%, 70%, or 90% maximum oxygen consumption (V ・ O 2max ).…”
Section: Other Biochemical Assaymentioning
confidence: 99%
“…The majority of studies have focused on aerobic (cardiovascular) exercise (31), with only three studies examining the effects of resistance (muscle strengthening) exercise, and these have reported contradictory effects (21,33,47). Resistance exercise is a key component of exercise recommendations for weight control (2) and public health (23, 42); thus, it is important to clarify the effects of resistance exercise on hunger and gut hormones.The effect of acute exercise bouts on total plasma ghrelin concentrations is controversial, with studies reporting no changes either during or postexercise (10,15,26,27,32,39,43,45,47), as well as increases (14,17,25,44) and decreases (21,33,48,50). Acylation of ghrelin is thought to be essential for appetite regulation because only the acylated form of the hormone can cross the blood-brain barrier (41).…”
mentioning
confidence: 99%
“…The effect of acute exercise bouts on total plasma ghrelin concentrations is controversial, with studies reporting no changes either during or postexercise (10,15,26,27,32,39,43,45,47), as well as increases (14,17,25,44) and decreases (21,33,48,50). Acylation of ghrelin is thought to be essential for appetite regulation because only the acylated form of the hormone can cross the blood-brain barrier (41).…”
mentioning
confidence: 99%